2020
DOI: 10.1021/jacs.0c05232
|View full text |Cite
|
Sign up to set email alerts
|

HIOx–IONO2 Dynamics at the Air–Water Interface: Revealing the Existence of a Halogen Bond at the Atmospheric Aerosol Surface

Abstract: Iodine is enriched in marine aerosols, particularly in coastal mid-latitude atmospheric environments, where it initiates the formation of new aerosol particles with iodic acid (HIO3) composition. However, particle formation in polluted and semipolluted locations is inhibited when the iodine monoxide radical (IO) is intercepted by NO2 to form the iodine nitrate (IONO2). The primary fate of IONO2 is believed to be, besides photolysis, uptake by aerosol surfaces, leading to particulate iodine activation. Herein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Finally, it is likely, and has indeed been shown theoretically that weak interactions, such as halogen and hydrogen bonding at aerosol surfaces can play a substantial role in determining heterogeneous reaction rates and mechanisms. [8][9][10][11] The chlorination reaction studied here is perhaps unique in that it is relatively slow reaction compared to others (e.g. ozonolysis and free radical reactions), thereby allowing the coupling and competition of the elementary steps shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is likely, and has indeed been shown theoretically that weak interactions, such as halogen and hydrogen bonding at aerosol surfaces can play a substantial role in determining heterogeneous reaction rates and mechanisms. [8][9][10][11] The chlorination reaction studied here is perhaps unique in that it is relatively slow reaction compared to others (e.g. ozonolysis and free radical reactions), thereby allowing the coupling and competition of the elementary steps shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction rate of a gas phase molecule with an aerosol or droplet surface is governed by a set of kinetic steps that include adsorption/desorption, solvation/de-solvation, and diffusion. [1][2][3][4][5] The relative rates and coupling of these steps can oen yield new pathways or catalytic mechanisms, [6][7][8][9][10][11][12][13] which are largely absent for a reaction occurring solely within a single phase. Given the central role that aerosols play in air pollution, 14,15 climate [16][17][18] and human health, 19 developing better insight, using laboratory measurements, 20 into the molecular factors that enhance, suppress or even catalyze multiphase chemical reactions is an important challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher level of theory calculations (CCSD(T)/aug-cc-pVTZ + LANL2DZ//M06-2X/aug-cc-pVDZ + LANL2DZ) confirmed that the reaction R3.1 , facilitated by the formation of a IO 3 –IONO 2 halogen-bonded adduct, is exothermic and barrierless. 33 This is not too surprising, considering that halogen bonding has been found to play an important role in the iodine CIMS when used for detecting HNO 3 . 34 Here, we have revisited our previous calculations 22 and extended them to reactions R6.2 , R3.2 , R3.3 , and R7 using the larger aug-cc-pVQZ basis set (see Methods).…”
Section: Discussionmentioning
confidence: 99%
“…Our ab initio calculations indicated that different reactions between I x O y with x = 2 and NO 3 – , Br – , CH 3 COO – , and H 3 O + are exothermic and can potentially generate some of the ions and cluster ions that have been attributed to HIO 3 , in particular IO 3 – and HIO 3 ·NO 3 – in the nitrate anion CIMS. 22 , 33 For example, …”
Section: Introductionmentioning
confidence: 99%